Semantic Analysis of al-'Afw as the Basic Principle of Forgiveness and Restorative Justice in the Qur'an - Khudzil Afwa; Kharis Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the semantic analysis of the Qur’an with the context of the word al-‘Afw, the purpose of this analysis is to know and understand the concept of the word al-‘Afw in the Qur’an based on Semantic review, by observing its various forms in the Qur’an. The word al-‘Afw which was investigated from the book al-mu’jam al mufahras li alfadz al-Quran al-karim was found 35 times scattered in 11 surahs with several different forms and mostly means forgiveness of sins. In assessing the meaning of al-‘Afw, the author uses a qualitative type of research and library research as a data collection method that aims to find meaning in depth. While the approach used in this study is to use Toshihiko Izutsu’s Quranic Semantics approach, as for the methodological steps, namely by showing the basic meaning, looking for relational meaning, paying attention to changes in the meaning of al-‘Afw through historical analysis, namely synchronic and diachronic, and the last step tracing the weltanschauung of the word al – ‘Afw. Al-'afw in the context of forgiveness also has a harmonious relationship with several terms in the Qur'an, namely shafa (leniency), ghafar (forgiveness) and taubah (repentance). These words have their own meaning.